Balance horizontal de líneas de ensamble para modelos mixtos (2015)
Traditionally assembly lines have been used to produce high volumes of a single model. To take advantage of these lines in flexible manufacturing environments, we can implement mixed model lines which allow manufacturing different products of a family in the same line, however, its balancing requires different techniques that traditional. In this research, a literature review was made to analyze the factors affecting the mixed model lines in MTO environments and based on this we developed a mathematical optimization model to stabilize workloads making easier the decision about production sequences that are programmed on the line. The model was run in several instances and the results were significantly better than those obtained with a line balancing traditional method.